Morphohistological study of testicles of the Brazilian diplopod Pseudonannolene tricolor Brolemann, 1901 (Pseudonannolenidae, Pseudonannolenida) - Fontanetti, C. S. (Assn Advan Zoology, 1998)
:The morphology and histology of testicles of the Brazilian species of diplopod Pseudonannolene tricolor Brolemann, 1901 are presented. The study is based in testicular vesicles that show differentiated spermatozoa in their interior.